Current-voltage characteristics of ballistic schottky barrier GNRFET and CNTFET: effect of relative dielectric constant - Ahmed, Sheikh Ziauddin; Shawkat, Mashiyat Sumaiya; Chowdhury, Md Iramul Hoque; Mominuzzaman, Sharif Mohammad (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 10th IEEE International Conference on Nano/Micro Engineered and Molecular Systems, NEMS 2015; Xi'an; China; 7 April 2015 through 11 April 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/NEMS.2015.7147449